The Role of Training Improvement Capacity and Local Cultural Influence on Behavioral Change in Village Government Apparatus: Peran Pelatihan Peningkatan Kapasitas dan Pengaruh Budaya Lokal terhadap Perubahan Perilaku Aparatur Pemerintah Desa - Ferdinand Kalesaran; Preysi Sherly Siby; Erens Prensius Sanggelorang; Joni Kutu’ Kampilong; Daniel Stevanus Imanuel Sondakh (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This research discusses the role of capacity-building training and local culture's influence in changing village government officials' behaviour. The main focus of this research is the importance of integrating technical and local cultural aspects in training to make it more effective and relevant. Training that only focuses on technical skills without paying attention to the local sociocultural context can cause resistance and be less accepted by officials and the community. On the other hand, training integrated with local cultural values ​​, such as cooperation and openness, increases the professionalism of the apparatus, improves the quality of public services, and strengthens public trust in the village government. This research uses a qualitative approach to understand the role of capacity-building training and the influence of local culture in changing apparatus behaviour. Data collection techniques include in-depth interviews, participant observation, and analysis of documents related to the training program. The primary informants for this research were the village head, village secretary, and village staff, who were selected purposefully to ensure the relevance of the data. Data analysis used NVivo 12 software with open and axial coding techniques to identify central themes and relationships between concepts. The research results show that the success of training is greatly influenced by its relevance to local culture and the ability of the apparatus to respond to community needs. This research recommendation includes the need for contextual, participatory and sustainable training design to achieve positive.